The Relationships Between Self-Concept and Self-Efficacy With Self-Management Among Elderly of Sanatoriums in Tehran - Mehran Kahe; Roshanak Vameghi; Mahshid Foroughan; Enayatollah Bakhshi; Vahid Bakhtyari (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives The present study determined the correlation of self-concept and self-efficacy with self-management among elderly in the sanatoriums in Tehran in2015. Methods & Materials This descriptive-analytic research, conducted in a cross-sectional study, enrolled 217 elderlies from the sanatoriums of Tehran in 2015 via a simple random sampling method. Three tools including Rogers self-concept scale, general self-efficacy scale (GSE-10), and self-management ability scale  (SMAS-30) were utilized to measure the variables. After sampling and gathering the questionnaires, collected data were entered into SPSS and analyzed using the analytical tests such as Kolmogorov–Smirnov test, Pearson’s test, and regression. Results The mean of self-concept, self-efficacy, and self-management were 8.25±1.47, 17.68±4.00, and 59.69±11.59 , respectively. Other findings indicated significant relationships of self-concept and self-efficacy with self-management (P<0.05). Multiple regression analysis showed that self-concept and self-efficacy could predict about 14% of self-management. Conclusion The elderly in the sanatoriums of Tehran had a low self-concept, self-efficacy, and self-management. Thus, it could be concluded that by improving the self-concept and self-efficacy of elderly, we might witness an increase in self-management.